Grenzwerstätze für additive Funktionen auf den geordneten Halbgruppen mit regulärer Normierung - Juškys, Z. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: З. Юшкис. Предельные теоремы для аддитивных функций, определенных на упорядоченных полугруппах с регулярной нормировкой Z. Juškys. Adityvinių funkcijų, apibrėžtų sutvarkytuose pusgrupiuose su reguliariu normavimu, ribinės teoremos